2021
DOI: 10.1038/s41598-021-86201-6
|View full text |Cite
|
Sign up to set email alerts
|

Virtual 2-D map of the fungal proteome

Abstract: The molecular weight and isoelectric point (pI) of the proteins plays important role in the cell. Depending upon the shape, size, and charge, protein provides its functional role in different parts of the cell. Therefore, understanding to the knowledge of their molecular weight and charges is (pI) is very important. Therefore, we conducted a proteome-wide analysis of protein sequences of 689 fungal species (7.15 million protein sequences) and construct a virtual 2-D map of the fungal proteome. The analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…The average isoelectric point of the virus proteome is in the acidic pI range ( pI 6.89), which is similar to average pI of the nuclear-encoded plant and fungal proteomes 27 , 28 . The average algal virus proteome had a pI of 7.08 and the vertebrate viral proteome had a pI of 7.09, both of which are in the basic range.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The average isoelectric point of the virus proteome is in the acidic pI range ( pI 6.89), which is similar to average pI of the nuclear-encoded plant and fungal proteomes 27 , 28 . The average algal virus proteome had a pI of 7.08 and the vertebrate viral proteome had a pI of 7.09, both of which are in the basic range.…”
Section: Discussionmentioning
confidence: 60%
“…The average number of amino acids per protein sequence in fungal and land plant viral proteomes were found to be 882.464 and 405.099, respectively. Notably, the average number of amino acids per protein in the nuclear-encoded (not from chloroplast or mitochondrial encoded) plant proteome was 424.34, while the nuclear-encoded (not from chloroplast) proteome of fungi was 459.319 27 , 28 . Interestingly, we found that fungal viruses encode larger proteins than the nuclear encoded proteins of its host.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations